2022
DOI: 10.1093/ageing/afac226
|View full text |Cite
|
Sign up to set email alerts
|

Using the recommended summary plan for emergency care and treatment (ReSPECT) in care homes: a qualitative interview study

Abstract: Background The Recommended Summary Plan for Emergency Care and Treatment (ReSPECT) is an advance care planning process designed to facilitate discussion and documentation of preferences for care in a medical emergency. Advance care planning is important in residential and nursing homes. Aim To explore the views and experiences of GPs and care home staff of the role of ReSPECT in: (i) supporting, and documenting, conversations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Indeed, an interview study of GPs and care home staff found that GPs value the input of care home staff in ReSPECT conversations. (18) Whilst care home staff were generally positive about being involved, they had concerns about taking responsibility for the form's content. (18).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, an interview study of GPs and care home staff found that GPs value the input of care home staff in ReSPECT conversations. (18) Whilst care home staff were generally positive about being involved, they had concerns about taking responsibility for the form's content. (18).…”
Section: Discussionmentioning
confidence: 99%
“…(18) Whilst care home staff were generally positive about being involved, they had concerns about taking responsibility for the form's content. (18).…”
Section: Discussionmentioning
confidence: 99%
“…Despite the centrality of patients and relatives to the ReSPECT process, no study so far has investigated patients’ and relatives’ experiences of ReSPECT in the community. In addition to our earlier programme of work, we have identified only one other qualitative study on the ReSPECT process; this study examined how general practitioners (GPs) and social care staff experienced ReSPECT in the care home context [ 9 ]. Moreover, a recent qualitative systematic review found only one study that focused on patient experiences of CPR-related conversations in the UK, predating the ReSPECT process [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Treatment escalation planning involves prospective decision-making regarding the range of increasingly intensive or complex interventions offered during an admission. Advance care planning (ACP) promotes shared decision-making, enabling patients to make informed choices about their future healthcare, including treatment escalation and end of life care [ 7 , 8 ]. However, ACP is poorly implemented in frailty with patients rarely given the chance to express their preferences [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, ACP is poorly implemented in frailty with patients rarely given the chance to express their preferences [ 9 , 10 ]. Emergency care and treatment plans, which summarise patient goals of care for emergency situations, have emerged to support acute decision-making but concerns about their use in practice include a tendency to focus solely on resuscitation decisions or end of life planning [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%